YOUTH POLICIES AND YOUTH PARTICIPATION (Annual of the Faculty of Philosophy in Skopje, 2022)
Through this research, an account is given of the existing differences in the perceptions of young people about the quality of life, the opportunities that young people have, as well as the ways in which young people make the choices that most affect their future, such as education, profession and personal development, and related to that what their environment offers. The research provides an overview of the biggest challenges faced by young people in different environments at the national level, and through the analysis of the obtained data, the research builds a comparative picture of the perceptions of the opportunities in the lives of young people in smaller and larger settlements in our country. Young people aged 15 to 29, who are the target group of this research, are a category of citizens that the state rarely sees separately from other categories of citizens. Even when it comes to creating policies aimed at young people, the state often takes a unified approach instead of putting into perspective the needs of young people from different backgrounds, such as young people from rural areas and small towns, young people with disabilities and young people from families with low incomes. With this in mind, it is easy to assume that young people whose “measures” are not used to make policies and solutions have fewer choices when it comes to educational opportunities, further opportunities for personal development and progress, opportunities for self-expression, as well as participation in cultural events. The lack of properly created policies for young people, in the field of education, employment or social protection, the low functionality of the institutions, contribute to the increase in the degree of youth emigration from the Republic of North Macedonia. Emigration, dissatisfaction, as well as the lack of communication about the active involvement of young people in democratic processes, are part of the factors that affect the stagnation of the social capital of young people in our country during the last ten years1. The absence of modern policies, strategies and documents that will improve the position of young people, through their effective involvement in decision-making in the educational process, at the local and national level, is something that has been a challenge for educational, local and national authorities over the years.
Keywords: youth policies; youth participation; quality of life